Electronic participation : 11th IFIP WG 8.5 International Conference, ePart 2019, San Benedetto Del Tronto, Italy, September 2-4, 2019, Proceedings /: 11th IFIP WG 8.5 International Conference, ePart 2019, San Benedetto Del Tronto, Italy, September 2-4, 2019, Proceedings. (2019) - Unknown
No abstract available